Model and method of information security managing for social groups in the implementation of the second stage of pension reform in Ukraine - Нікіфорова, Лілія Олександрівна; Яремчук, Юрій Євгенович; Шиян, Анатолій Антонович (Ukrainian Scientific Journal of Information Security, 2014)
The introduction of the second stage of the pension reform in Ukraine requires a specially organized informational support, which should counteract against negative information-psychological factors, which occur today in Ukraine. In fact, a new financial institution, which is particularly vulnerable to negative information-psychological impact, will be created. The paper constructs a model for information security management during implementation and operation of the second stage of the pension reform in Ukraine. The model’ purpose is to reconcile the interests of pension fund’ workers and businessmen, and the result of such coordination should satisfy for investors. In this model the game theory is used, and salvation model is carried out by Stackelberg, when the investor has the power. Then the players (“pension fund” and “enterprise”) solution is in the form of Nash equilibrium. In the model the inequalities found, to which the characteristic performance of the pension fund and the company to investors be met. Under these inequalities the investors can to receive the highest level of security, and the state can to receive the highest growth of the public good, respectively. The key elements for a method for managing information security during the formation and operation of the second stage of the pension reform in Ukraine are established.